ANALISIS BEBAN KERJA UNTUK MENENTUKAN JUMLAH TENAGA KERJA OPTIMAL DI DINAS KOPERASI DAN USAHA MIKRO KOTA DEPOK DENGAN METODE WORK SAMPLING - Sista Fitri Amarko (2023)
The Office of Cooperatives and Micro Enterprises for the City of Depok has the task of assisting the Mayor in carrying out government affairs in the field of cooperatives and micro enterprises and assistance tasks assigned to the City Regions. The work carried out by employees is work that requires accuracy, patience, skill, and responsibility, thus indicating fatigue due to work. Which is based on the Subjective Self Rating Test questionnaire to measure work fatigue resulting in moderate level of work fatigue. One of the factors causing work fatigue is due to the influence of workload. So, it is necessary to measure the workload to determine the optimal number of workers, which is measured using the Work Sampling method. After processing the data using the Work Sampling method, the results for the number of workers should be within good limits, namely 4 people for the Planning, Evaluation and Reporting Sub-Division; as many as 9 people for the Finance and Assets Sub-Division; as many as 3 people for the General and Personnel Sub-Division; as many as 11 for the Institutional and Human Resources Sector; as many as 27 people for the Empowerment and Development of Micro Enterprises; and as many as 43 people for Supervision and Business Development. So that the total addition of the number of workers is as many as 59 people.